Continuous flow solvent-free and catalyst-free mechanochemical production of rhodamine B dyes and their derivatives - Purohit, Mukesh; Shaikh, Tabrez Rafique; Kulkarni, Amol A. (Chemical Communications, 2025)
In this communication, we have described a simple and efficient, catalyst free and solvent-free protocol for the continuous flow synthesis of rhodamine B dyes developed from 3-diethyl amino phenol and phthalic anhydride. Nearly 95% conversion was achieved within 12 min using a jacketed single screw reactor. This method is further used for the synthesis of six derivatives with 70-84% yield, which can be compared to 85% yield from a 1-hour long batch synthesis involving a catalyst.